2000
DOI: 10.1590/s1415-47572000000300006
|View full text |Cite
|
Sign up to set email alerts
|

FISH studies in a girl with sporadic aniridia and an apparently balanced de novo t(11;13)(p13;q33) translocation detect a microdeletion involving the WAGR region

Abstract: Conventional cytogenetic studies on a female infant with sporadic aniridia revealed what appeared to be a balanced de novo t(11;13) (p13;q33) translocation. Fluorescence in situ hybridization (FISH) investigations, however, detected the presence of a cryptic 11p13p14 deletion which included the WAGR region and involved approximately 7.5 Mb of DNA, including the PAX6 and WT1 genes. These results account for the patient's aniridia, and place her at high risk for developing Wilms' tumour. The absence of mental re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…including deletions, both visible and cryptic (Mannens et al 1991;Fantes et al 1992Fantes et al , 1995aDreschler et al 1994;Kent et al 1997;Crolla et al 1997;Grønskov et al 2001;Muto et al 2002), and inversions, translocations, and insertions (Simola et al 1982;Moore et al 1986;Mannens et al 1991;Fantes et al 1995b;Crolla et al 1996Crolla et al , 1997Llerena et al 2000), have also been reported in association with both isolated sporadic and familial aniridia, as well as in patients with WAGR syndrome. More recently, cell hybrid studies demonstrated inactivation of two independent, aniridia-associated PAX6 alleles, each carrying an ∼1,000-kb submicroscopic deletion distal to PAX6, with the proximal breakpoints at ∼11 kb and ∼22 kb 3 of the PAX6 polyA addition site (Lauderdale et al 2000).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…including deletions, both visible and cryptic (Mannens et al 1991;Fantes et al 1992Fantes et al , 1995aDreschler et al 1994;Kent et al 1997;Crolla et al 1997;Grønskov et al 2001;Muto et al 2002), and inversions, translocations, and insertions (Simola et al 1982;Moore et al 1986;Mannens et al 1991;Fantes et al 1995b;Crolla et al 1996Crolla et al , 1997Llerena et al 2000), have also been reported in association with both isolated sporadic and familial aniridia, as well as in patients with WAGR syndrome. More recently, cell hybrid studies demonstrated inactivation of two independent, aniridia-associated PAX6 alleles, each carrying an ∼1,000-kb submicroscopic deletion distal to PAX6, with the proximal breakpoints at ∼11 kb and ∼22 kb 3 of the PAX6 polyA addition site (Lauderdale et al 2000).…”
Section: Figurementioning
confidence: 99%
“…The fourth chromosomal rearrangement, an apparently balanced t(11;13), was found by FISH to have an ∼7.5-Mb deletion at the breakpoint on the der(11) (Llerena et al 2000).…”
Section: Chromosomal Rearrangementsmentioning
confidence: 99%